Penentuan Konstanta Resesi Hidrograf Menggunakan Metode Plot Semi Logaritmik (Studi Kasus di Sub DAS Goseng) - Putu Sudira; Sukresno .; Elly Kurniawati (Jurnal Keteknikan Pertanian, 2009)
Recession curve is a spesific part of stream hygrograph after it reachs peak flow and it represents the withdrawal of groundwater from storage. Daily recession constant of surface runoff, interflow, and baseflow have been derived for 15 segments on Goseng subwatershed with area approximately 596 ha.Semi logarithmic plot is recession analysis method which plotting stream discharge in y-ordinate and time in x-coordinate in semi logarithmic scale. The start of time recession is denoted by a straight line in the graphic. This method was used for separating a hydrograph into linear components of surface runoff, interflow, and baseflow. The results of the research shows that recession segment from daily hydrographhas short time and does not have all three stream components. A short segment can only be divided into two flow components. Separation pattern for water catchment area are baseflow-interflow, baseflow-surfacerunoff, and interflow-surface runoff. Recession constant value differ from year to year but the differences do not have great influence in determining the average value of recession constant.Keywords : surface runoff, interflow, base flow, recession constant, semi logarithmic plotDiterima: 26 Agustus 2008; Disetujui: 3 Pebruari 2009